PERAN WEBSITE KOMINFO TANAH DATAR DALAM PENYEBARAN INFORMASI KINERJA PEMERINTAH DAERAH TANAH DATAR - Nurjanah, Titi; Rikarno, Riki (KINEMA: Jurnal Komunikasi dan Penyiaran, 2024)
The main problem in this thesis is how the role of the Tanah Datar Kominfo website in disseminating information on the performance of the Tanah Datar local government. This study aims to identify and describe the role of the website in disseminating information on the performance of the Tanah Datar local government. The research method used is qualitative with a descriptive approach. Data collection techniques in this study were by means of observation, interviews, and documentation in the form of pictures and sound recordings. The role of website communication media in this study as a means of information on the performance of the Tanah Datar local government. The results showed that the role of the Tanah Datar Kominfo website in disseminating information on the performance of the Tanah Datar regional government is as information, the information is in the form of the performance of the regional government both in terms of politics, economics, social and culture, on the website there is also information about scholarships opened by the local government to help the education of students and flat land students. The obstacle faced by the website admin or local government in managing this website is the large number of readers who do not leave traces in the form of likes, suggestions or input. The obstacle faced by the community in general is the emergence of boredom when reading due to the lack of supporting images in the news.